The Effect of Students’ Anxiety, Learning Discipline, and Learning Motivation on Students’ Mathematic Learning Outcomes in Vocational High School - Komang Agus Adi Saputra; I Gede Ratnaya; I Gusti Lanang Agung Parwata; Ni Ketut Widiartini (Jurnal Pendidikan dan Pengajaran, 2023)
The low student mathematics learning outcomes are caused by several factors such as students' anxiety, learning discipline, and learning motivation. The study was aimed to analyze the effect of students’ anxiety, learning discipline, and learning motivation towards students’ mathematic learning outcomes.  The research design was in the form of ex post-facto by involving 235 vocational high school students. They were selected by using proportional random sampling. The data were obtained by conducting test and non-test technique. The test was conducted to obtain the students’ learning outcomes meanwhile the questionnaire was distributed to the students to gather their anxiety, learning discipline, and learning motivation. The research instruments were test and questionnaire. The obtained data were analysed through structural equation modelling (SEM). The result showed that;  1) there  was a positive effect of learning discipline on students’ mathematic learning , 2) there was a negative effect of students’ anxiety on students’ learning discipline, 3) there  was a direct negative influence contributed by students’ anxiety towards students’ learning motivation, 4) there was a direct positive effect of students’ learning motivation on students’ learning discipline, 5) there was a direct positive effect of learning motivation towards students’ mathematic learning outcomes, 6) there was a direct negative effect of anxiety on students’ learning discipline, and 7) there was indirect positive effect of learning motivation on students’ mathematic learning outcomes through learning discipline.